Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation untuk Meningkatkan Hasil Belajar Peserta Didik - Ibrahim, Rachmat Arif (Ridwan Institute, 2021)
Class Action Research with the aim to know the model of Cooperative Learning Type Investigation Group can be the result of learning students on redox reaction material and electrolysis class XII IPA-1 SMA Negeri 2 Leuwidamar. Ongoing learning Investigation Group Hoping to be the results of learning students class XII IPA-1. Which variables are the Use of Cooperative Model Learning Type Investigation Group (X) and Learner Learning Outcomes (Y). Which data are qualitative and quantitative data from the results of Final Research I, II and Grade III through the Education Process in Class XII IPA-1 SMA Negeri 2 Leuwidamar Lebak Regency. The results of the study concluded that Cooperative Learning Type Investigation Group is very and interesting for learning learning. The result of the following data : a. Activity level is good from the average age I value of 42.85% , among which is 59.52% and age iii by 90.48% ; B. Teacher planning in the time carried out in the course of healthy quarter I score 4.58, score ii at 4.68 and grade III score 5.00 and Communication process on on score I 3.78, on score II 4.35 and score III 4.75; score 4.75 ; score score c. Student learning outcomes, before complete education students there are 5 (14.29%), life I there are 11 (31.43%), grade II there are 18 (51.43%) and among others there are 30 (85.71%). So it can be concluded that the use of Model Learning Type Investigation Group can increase the activities of students who are in the aftermath of the results of learning.